Extended extraocular phenotype of PROM1 mutation in kindreds with known autosomal dominant macular dystrophy. - Arrigoni, F; Matarin, M; Thompson, P; Michaelides, M; Mcclements, M; Redmond, E; Clarke, L; Ellins, E; Mohamed, S; Pavord, I; Klein, N; Hunt, D; et al. (2011)
Mutations in prominin 1 (PROM1) have been shown to result in retinitis pigmentosa, macular degeneration and cone-rod dystrophy. Because of the putative role of PROM1 in hippocampal neurogenesis, we examined two kindreds with the same R373C PROM1 missense mutation using our established paradigm to study brain structure and function. As the protein encoded by PROM1, known as CD133, is used to identify stem/progenitor cells that can be found in peripheral blood and reflect endothelial reparatory mechanisms, other parameters were subsequently examined that included measures of vascular function, endothelial function and angiogenic capacity. We found that aspects of endothelial function assayed ex vivo were abnormal in patients with the R373C PROM1 mutation, with impaired adhesion capacity and higher levels of cellular damage. We also noted renal infections, haematuria and recurrent miscarriages possibly reflecting consequences of abnormal tubular modelling. Further studies are needed to confirm these findings.